One-year quality of life among post-hospitalization COVID-19 patients - Pérez Catalán, Ignacio; Roig Martí, Celia; Fabra Juana, Sergio; Domínguez Bajo, Elena; Herrero Rodríguez, Germán; Segura Fábrega, Ana; Varea Villanueva, María; Folgado Escudero, Sofía; Esteve Gimeno, María José; Palomo de la Sota, Daniela; Cardenal Álvarez, Alejandro; Mateu Campos, María Lidón; et al. (Frontiers in Public Health, 2023)
Introduction. The long-term effects of SARS-CoV-2 are unclear, as are the factors influencing the evolution. Objective: to assess healthrelated quality of life one year after a hospital admission due to COVID-19 and to identify factors that may influence it. Material and methods. Retrospective observational study in a tertiary hospital from March 2021 to February 2022. Inclusion criteria: ≥18 years old and admitted for SARS-CoV-2 infection. Exclusion criteria: death, not located, refusal to participate, cognitive impairment, and language barrier. Variables: demographic data, medical history, clinical and analytical outcomes during hospital admission, treatment received, and vaccination against SARS-CoV-2 following admission. Participants were interviewed by phone one year after admission, using the SF-36 quality of life questionnaire. Results. There were 486 included patients. The domains yielding the lowest scores were general health (median 65%, interquartile range [IQR] 45-80), vitality (median 65%, IQR 45-80), and mental health (median 73.5%, IQR 60-100). Multivariable analysis showed that female sex and fibromyalgia/fatigue had a negative influence on all domains. Obesity was associated with worse outcomes in physical functioning, physical role, bodily pain and vitality. Other factors associated with worse scores were an older age in physical functioning and high age-adjusted Charslon comorbidity in physical functioning and general health. Age was associated with better results in emotional role and High C-reactive protein at admission on vitality. Conclusion. One year after admission for COVID-19, quality of life remains affected, especially the domains of general health, vitality, and mental health. Factors associated with worse outcomes are female sex, fibromyalgia/chronic fatigue, and obesity.